(untitled) (Revista Sistemas de Producción Agroecológicos, 2017)
The cultivation of natural rubber in Colombia has shown remarkable growth in recent years, due to its large participation in the processing industry being key raw material for a wide variety of finished products ranging from specialized applications such as tires, even toiletries for mass consumption as gloves, therefore, this work aimed to publicize the cultivation of rubber (Hevea brasiliensis) in its stages of nursery and early establishment in the municipalities of Paratebueno (Cundinamarca) and Mapiripán (Meta), making a tour by the different activities that take place in the production and showing some results obtained in them, as evaluations that were carried out in the nursery as a learning method and possible solutions to problems that arise in a timely manner, finally the results obtained from the activities and evaluations were analyzed, generating elements and knowledge that allow deeper into the subject. It is concluded that the rubber nursery established in the municipality of Paratebueno has the appropriate conditions for its growth, not only because of its geographical location, but also the good agronomic activities that develop such as fertilization, watering in summer time, weed control and daily monitoring of integrated management of pest and disease; in addition, the nursery and the two years old plantation are in excellent condition, because the observations in the crop are constant, with which it manages to avoid possible damage from pests and diseases, and correct nutritional deficiencies.